METATHESIS IN NIGERIAN ENGLISH ACCENT (NEA): A COMPARATIVE STUDY OF GENERATIONS X AND Z - ANABA , Elizabeth Ezenwanyi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
Despite literature mentioning metathesis as far back as the 20th century, the phenomenon remains one of the least researched phonological processes. The process has received little to no attention, especially in an ESL setting, and this is the first empirical study of metathesis in Nigeria. Thus, this research investigates metathesis as a simplifying strategy in Nigerian English Accent (NEA). The objectives are to examine whether the phenomenon is a regular process, to detail its typology in Nigeria, and to compare metathetical frequency between generations X and Z. Data for the research were collected using 18 sentences enunciated by 60 teachers in public and private schools (30 from each school). Findings revealed that metathesis is a regular process that occurs in complex syllabic structures and interacts with other phonological processes. Findings also showed that metathesis occurs more frequently among Generation Z than Generation X. CC (consonant-consonant) metathesis and CV (consonant-vowel) metathesis in adjacent and long-distance typologies were also identified. It was also revealed that inflectional markers are often eliminated or undergo other phonological processes in cases of CCC sequence, to achieve “ease of articulation”.